(untitled) (IITM Journal of Business Studies, 2024)
Financial literacy and knowledge lead to perceived financial understanding. These contribute to the decision-making for savings and investments. Such literacy is a function of awareness, experience, and skills. Financial literacy forms a positive financial attitude towards the achievement of financial goals and freedom. The level of financial literacy of an individual makes them more rational in making their financial decisions. Having good financial knowledge and understanding would help in the management of their finances and further planning of their money in a better way. This study is descriptive in nature. In this study, a structured questionnaire was used to measure the financial literacy of the young investors ranging between the ages of 18 to 35. The sample size of the study is 390. The data were collected with the help of a structured questionnaire. With the help of “Exploratory Factor Analysis” and “Multiple Regression Analysis,” it was found that there is a significant impact of Financial Literacy (Financial Behavior, Financial Attitude, Financial Knowledge-Basic, and Financial Knowledge-Advanced) on the investment behavior of young investors in India.